A presentation of penile siliconoma in primary care after a dubious implant injection: a case report - Abdul Manap, Abdul Hadi; Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Nik Hisyamuddin Fathi, Nik Qisti Fathi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Cases of penile siliconoma are unusual and less commonly present to medical practitioners. The siliconoma is a subsequence of injecting high viscous solution into the penis; commonly sillicone with the aim to enhance its size and performance. This case will look at a patient who developed penile siliconoma after a dubious penile implant injection gone wrong. It will also look at what surgical options are available to the unfortunate patients to ease their suffering. Physician should have a high index of suspicion on the use of such substances to enhance sexual performances in patients presenting with atypical penile swelling.